Frequency of different types of domestic violence in antenatal patients - Gul, Sara; Zeb, Laila; Faiz, Nasreen Ruby (Journal of Postgraduate Medical Institute, 2013)
Objectives: To determine the frequency of different types of domestic violence in antenatal patients. Methodology: A cross-sectional hospital-based study was done at Obstetrics and Gynaecology Department,Lady Reading Hospital from April 2010 to March 2011. Patients received in antenatal clinic were enrolled.Informed consent was taken from the participants meeting the inclusion criteria. The tool used to measureabuse was derived from the Abuse Assessment Screen. Results: A total of 129 of pregnant women participated in this study. The respondents were young (averageage 31 years). One hundred thirteen (87.6%) had length of marriage more than one year. Ninety six(74.4%) were multipara and Sixty six (51.2%) were in third trimester. Among them 53.5% were abused (anytype) in marital lifetime and 39.5% experienced physical violence last year. Forty six (35.7%) respondentswere abused physically during pregnancy. Verbal violence was 51.9%, followed by emotional violence46.50%, economic violence 33.3%, and 20.40% had nonconsensual sex (sexual violence). Husband wasinvolved directly in 38.0% cases, while in-laws in 20.2% cases. Violence during pregnancy was associatedwith marital life-time violence and physical violence during last year (p < 0.05). Conclusion: Domestic violence during pregnancy is a common problem and highlights the need for interventionsby health professionals.